A closed-loop frequency domain PI retuning technique for multivariable systems. Issue 3 (2021) - de A Aguiar, Anna Paula V; Júnior, George Acioli; Barros, Péricles R; Perkusich, Angelo
Abstract: A Proportional-Integral (PI) controller frequency domain retuning technique for square multivariable process is presented in this paper. Assuming knowledge of the current PI controller, the controller gains increments are computed in such that the new closed-loop matches with a desired reference model. This is performed using only the closed-loop response at certain frequencies, without knowledge of the process model. Effectiveness of the proposed method is shown in the simulation results. The maximum singular value is used to show the robustness. Finally, an experimental result is presented.